HUBUNGAN HUKUM ANTARA PEMILIK KENDARAAN DENGAN PENGELOLA PARKIR - Parmitasari, Indah (Jurnal Yuridis, 2016)
The use of standard agreements are now widely applied in the business world,including the parking agreement set forth in the form of a parking ticket. Parking ticket in the transition of responsibilities are standard clause which reads as follows: "The management of parking is not responsible for loss or any damage, "The management of parking is not responsible for any loss or damage to the vehicle". The existence of this clause resulted in problems of parking management accountability to the consumer. This raises the issue of research, (1) whether the legal relationship that occurs between park managers and consumers? (2) how the parking management responsibilities to the loss of the vehicle and or property of consumer goods in the parking lot of standard clauses related to the transfer of responsibility for the parking ticket?. This study aims to determine the relationship between the law of what is happening parking managers and consumers in business transactions parking and parking management form of responsibility in case of loss of the vehicle and orproperty of consumer goods in the parking lot is related to the standard clause transition of responsibilities the parking ticket. This research is a normative law with qualitative analysis. The study concluded, legal relationships that occur between parking management and customer care is the relationship agreement goods (vehicles), and parking management shall be responsible for the loss of the vehicle and or property of consumers who parked in the parking area management.